Misi Kemanusiaan Melalui Program Bantuan Sembako Dan Pengobatan Gratis Bagi Masyarakat Di Desa Muka Paya Kecamatan Hinai - azhar; Safitri; Abdul Hamid; Nurul Putri Aulia (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
Muka Paya Village, located in Hinai District, is one of the villages that faces major challenges in terms of economy and access to health services. Most of the villagers rely on the agricultural sector as their main source of income, but the unstable agricultural output often means that their income is not enough to meet their daily needs. In addition, access to adequate health facilities is still limited, with many residents having difficulty obtaining quality medical services. Seeing this reality, a humanitarian mission through a food aid program and free medical treatment is very important to carry out. This program aims to provide direct assistance to the people of Muka Paya Village in the form of food aid covering basic necessities such as rice, oil, sugar, and other needs. In addition, the free medical treatment program is expected to provide decent access to health for underprivileged residents, so that they no longer need to worry about high medical costs